Gut microbiota associated with cryptococcal meningitis and dysbiosis caused by anti-fungal treatment - Li, Hang; Zhang, Lei; Zhang, Keming; Huang, Yue; Liu, Yi; Lu, Xiaodi; Liao, Wanqing; Liu, Xiaogang; Zhang, Qilong; Pan, Weihua (Frontiers in Microbiology, 2023)
The gut microbiota is a dynamic and highly diverse microbial ecosystem that affects many aspects of the host’s physiology. An improved understanding of the gut microbiota could lead to better strategies for the diagnosis and therapy of cryptococcal meningitis (CM), but the impact of Cryptococcus infection and anti-fungal treatment on the gut microbiota has rarely been studied. We characterized the diversity and composition of the gut microbiota in CM patients at diagnosis and healthy controls (HCs) using metagenomic sequencing and determined the effects of anti-fungal drugs. We found that CM patients had distinct bacterial and fungal compositions compared with HCs, with eight differentially abundant fungal and 72 differentially abundant bacterial species identified between the two groups. CM patients showed an increased abundance of Enterococcus avium, Leuconostoc mesenteroides, and Weissella cibaria, and a decreased abundance of Prevotella spp. compared with HCs. However, anti-fungal treatment only led to minor changes in the intestinal microbiota. Moreover, both positive and negative correlations existed in fungal, bacterial, and clinical indicators. Our study suggests that the Cryptococcus neoformans infection caused a distinct dysbiosis of the gut microbiota and contributes valuable information implying potential links between the CM and gut microbiota.